INFLUENCE OF RANGE OF MOTION(ROM) ONMUSCLE STRENGTH POST STROKE PATIENTS: INFLUENCE OF RANGE OF MOTION - harun Harun AlRasid; julianto Julianto Laia; ratih Ratih Suryaman; retno Retno Dwi Santi (Jurnal Ilmiah Wijaya, 2020)
Basedon WHO (World Health Organization) data, stroke is the third leading cause of death and the sixth most common cause of disability. About 15 million people suffer their first stroke every year, with one third of these cases or around 6.6 million resultin in death (3.5 million women and 3.1 million men). Stroke is a huge problem in developing countries compared todeveloped countries. More than 81% of deaths from stroke occur in developing countries, the percentage of premature deaths due to stroke rises to 94% in people under the age of 70. This study aim stodetermine whether there is an effect of Range of Motion (ROM) on the muscle strength of post-stroke patients at Leuwiliang District Hospital clinic in 2019. This research is categorized as a quantitative study with a Pre-experimental Design research design with the One Group Pre-test-Post-test Design method and is carried out at the Leuwiliang District Hospital out patient clinic from September 11 until September 18 2019 witha population of 19 and asample of 1